Tinjauan Atas Sistem Penerimaan Kas Dan Pengeluaran Kas Pada Klub Golf Bogor Raya - Putri, Firli Febiyoti; Supriadi, Yoyon; Muktiadji, Nusa; Nurisnaini, Neni (Jurnal Aplikasi Bisnis Kesatuan, 2023)
ABSTRACTIn the process of cash receipts and cash disbursements, it is necessary to have an appropriate system so that the implementation can be carried out smoothly. As with cash receipts and cash disbursements, they must have complete books and records so that the cash receipts system and cash disbursement system can be controlled properly.The purpose of the discussion in this study is to find out how the cash receipts system and cash disbursement system exist at PT. Bogor Raya Development (Bogor Raya Golf Club). To achieve clear and directed discussion targets, the authors formulate problems regarding the Cash Receipt System, Cash Disbursement System, the constraints that arise in the implementation of cash receipts and cash disbursements, and how the solution is to resolve these obstacles.The results that have been discussed show that cash receipts at PT. Bogor Raya Development (Bogor Raya Golf Club) is sourced from cash sales or payments by receivables from restaurants and proshops, payment of golf membership fees and from wedding event reservations. While cash disbursements at PT. Bogor Raya Development (Bogor Raya Golf Club) is carried out only for the company's operational activities and is recorded in the company's bookkeeping system.Keywords : Cash, Cash Receipt, Cash Disbursement.